Konsep Psikologi Islam Dalam Pandangan Abdallah Rothman dan Coley - Faisal Anwar; Putry Julia; Ifanna Ifanna (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This research aims to examine the views of Abdallah Rothman and Coley on Islamic psychology and the extent to which their approach depicts Islamic psychology within the human self. This study is a qualitative research with a literature review design that analyzes the works of Rothman & Coley on Islamic psychology as the main source of this research. The results of the analysis reveal four main categories in Islamic psychology: 1) Soul Nature (fitrah, relationship with God), 2) Soul Structure (nafs, qalb, aql, ruh), 3) Soul Levels (nafs al-ammarah, nafs al-lawwama, nafs al-mutmainnah), and 4) Soul Development (tazkiyat an-nafs, jihad an-nafs, tahdhib al-akhlaq). The conclusion of this research emphasizes the importance of focusing on the purification of the soul through tazkiyatun nafs and its relationship with psychotherapy. Rothman & Coley's views on Islamic psychology depict the human fitrah connected to God, facing internal conflicts between low desires and goodness, and the journey of soul development from nafs al-ammarah to nafs al-mutmainnah. The concept of soul purification (tazkiyatun nafs) plays a central role in achieving harmony with fitrah and overcoming internal conflicts within the soul.